A lab-based comparison of differential ratings of perceived exertion between a run and jump protocol involving low or high impacts on the lower extremities. Influence of impacts on differential RPE - Houtmeyers, K. C.; Brink, M. S.; Helsen, W. F.; Haelewijn, N.; Hagen, M.; Jaspers, A.; Vanrenterghem, J. (European Journal of Sport Science, 2023)
The rating of perceived exertion method allows to describe training intensity in a single value. To better understand the underlying components, the separate rating of perceived breathlessness (RPE-B) and leg-muscle exertion (RPE-L) has been proposed. Here we hypothesized that the separation between the two components may (partly) be determined by the impacts on the lower extremities. In this study, we aimed to experimentally evaluate the differential effect of high versus low impact running and jumping on RPE-B and RPE-L in team sport activities by manipulating the movement strategy (heel strike and passive landing pattern versus forefoot strike and active landing pattern). Eighteen recreational team sport players participated in two submaximal tests consisting of a sequence of running and jumping bouts, whilst ground reaction forces (GRF) were collected. RPE-B and RPE-L data were collected after each bout using the CR100 scale. Paired-samples t-tests were used to analyse between-session differences in these variables. GRF analysis showed that absorption mechanics differed considerably between the two sessions. RPE-L was on average 6.50 AU higher in the low impact session (p = 0.006). However, RPE-B was also increased by 4.96 AU with low impact (p = 0.009). We conclude that the extent to which the lower extremities are being exposed to high or low impacts does not explain a possible separation between the two RPE types.